PANDUAN PERANCANGAN SPASIAL, FURNITURE DAN ELEMEN INTERIOR COMMUNITY KITCHEN BERBASIS EMPATI Studi Kasus : Community Kitchen Foodcycle Indonesia: PANDUAN PERANCANGAN SPASIAL, FURNITURE DAN ELEMEN INTERIOR COMMUNITY KITCHEN BERBASIS EMPATI Studi Kasus : Community Kitchen Foodcycle Indonesia - Dedrina Aurya Syazira (Universitas Telkom, 2025)
Abstract : A community kitchen is a collective space that serves not only as a place for cooking, but also as a venue for social collaboration, interaction among users, and a means of community empowerment. In the context of the community kitchens operated by FoodCycle Indonesia, the complexity of activities and the diversity of users’ backgrounds present unique challenges in designing the space and furniture to meet users’ needs. This study aims to develop a design strategy for the space, furniture, and spatial elements that can address the functional and user needs of a community kitchen. Using a design thinking approach and qualitative case study methods, this study focuses on identifying activity patterns, spatial issues, and the strategic roles of the space and furniture in supporting work efficiency and user comfort during various activities in the community kitchen. The process of finding solutions was conducted in depth through the “empathize” phase to fully understand user needs through observation, interviews, and questionnaires. The results of this research were formulated into a design strategy for flexible spaces and furniture that adapts to the evolving activities in the community kitchen, taking into account aspects such as activities and needs, ergonomics, anthropometry, materials, and other interior design elements, while supporting the kitchen’s long-term operations. This study is expected to produce design recommendations that can create an inclusive workspace, improve work quality, and enhance the efficiency of workflows within community kitchen facilities. Keywords: Community kitchen, spatial and furniture design strategies, design thinking, empathy, design guidelines